Struktur Populasi Kecapi (Sandoricum Koetjape (Burm.F.) Merr) Di Bantaran Sungai Barito Desa Sungai Gampa Kabupaten Barito Kuala - Annisa Fitriani Azzahra; Dharmono, Dharmono (Biospecies, 2025)
The population structure of plants is a critical area of study in ecology, essential for understanding the dynamics of plant assemblages. Sandoricum koetjape (Burm.f.) Merr, commonly known as kecapi, is a plant species found along the banks of the Barito River in Sungai Gampa Village. This study aims to describe the population structure of kecapi (Sandoricum koetjape (Burm.f.) Merr)   in this riparian area. The research employed the cruise method within an area spanning 3 km in length and 50 meters in width from the riverbank, with population data based on the classification by Odum (1993). The results showed that the population structure consists of 98.68 individuals/km² (pre-reproductive), 171.05 individuals/km² (reproductive), and 26.31 individuals/km² (post-reproductive), forming an urn-shaped pyramid indicative of a disturbed population, however, the kecapi population is considered stable and not in a critical condition, as more than 25 mature individuals were found per square kilometer.